Weak Boundedness for Commutators of $n$-Dimensional Hardy-Type Operators on Mixed Herz Spaces (Analysis in Theory and Applications, 2026)
In this paper, we obtain the boundedness for the commutators of $n$-dimensional Hardy-type operators from mixed Herz spaces to weak mixed Herz spaces, where the symbol functions are in the intersection of the mixed central bounded mean oscillation space $\text{CBMO}_{\vec{q'}}(\mathbb{R}^n)$ and the weak mixed central bounded mean oscillation space $W_{\vec{q}}(\mathbb{R}^n)$.
Keywords: Weak mixed central bounded mean oscillation space; $n$-dimensional Hardy-type operators; commutator; weak mixed Herz space